Evaluation of cervical sagittal parameters on supine magnetic resonance imaging in patients with Chiari I malformation without syringomyelia - Karabağ, H.; İplikçioğlu, A.C. (Neuro-chirurgie, 2022)
The current study aimed to assess the effects of tonsillar herniation on cervical alignment in Chiari I patients without syringomyelia using new cervical sagittal alignment parameters, such as C0–2 Cobb angle, C2–7 cobb angle, T1 slope, and C2–7 sagittal vertical axis (SVA). Two spinal surgeons independently evaluated midline T2-weighted sagittal magnetic resonance imaging findings of 28 Chiari I patients without syringomyelia and 40 patients without tonsillar herniation but with similar complaints. Thereafter, the measured C0–2 Cobb angle, C2–7 Cobb angle T1 slope, and C2–7 SVA were compared using the t-test. Differences in the mean values for C2–7 Cobb angle, T1 slope, and C2–7 SVA were found between Chiari I patients and those without tonsillar herniation. The current study showed that Chiari I patients were less lordotic (kyphotic) compared to subjects without tonsillar herniation.